Sediaan Obat Kumur Dalam Bentuk Teh Celup Dari Daun Teh Hijau, Daun Sirih, Dan Kayu Manis - Rully Dwi Wahyuningrum; Devi Tirta Sari; Putri Andyn Maharani; Reza Aprilia Putri (UNIVERSITAS PGRI MADIUN, 2023)
Mouthwash is a solution or liquid used to rinse the oral cavity that has benefits for eliminating harmful bacteria, removing unpleasant odors (halitosis), providing therapeutic effects, and eliminating or preventing dental caries, as well as for aesthetics and freshness. (Salimah 2018). Mouthwash can also be used as an anti-inflammatory and topical analgesic agent. The aim of this project article is to understand how to make mouthwash using ingredients such as green tea leaves, betel leaves, and cinnamon to reduce bad breath. The method used in this study is an action research method, conducted from November to December 2023 in Biology Laboratory 2, Campus 1, PGRI Madiun University, utilizing Google Scholar, Science Direct, and Semantic Scholar, which provided scientific articles and journals from the last 10 years as guidance and reference for the creation of this project. Regarding the process that has been examined, it began with searching for a journal focused on the keyword traditional mouthwash, and then referring to sources that align with the significant methodological objectives. Based on the results of the mouthwash preparation project in the form of tea bags, the most favored technique was the preparation in treatment 1, which was stored at a cold temperature of 8ËšC. The results from the combination that was carried out, namely 2g of cinnamon, 2g of green tea leaves, and 1g of betel leaves, were well received.Keywords: Mouthwash, Bad Breath, Green Tea, Cinnamon, and Betel Leaf.